Fuzzy logic-based transmission power control algorithm for energy efficient MAC protocol in wireless sensor networks. (1st January 2012) - Sabitha, Ramakrishnan; Thyagarajan, Thangavelu
In this paper, we investigate the impact of a fuzzy logic control-based transmission power control in a wireless sensor network on the quality of service aspects like average power, energy efficiency, throughput and average end-to-end delay. The transmission power control algorithm is implemented in the medium access control layer as an enhancement for wireless MAC Standard IEEE 802.15.4. For a given fading channel, observations are made regarding received signal strength variations and link quality variations for different distances of separation between transmitter and receiver. The membership functions for the fuzzy logic are then formulated for efficient transmission power control. The transmission power of the source node along with the received signal strength indicator and link quality indicator values measured at the receiving node is used for deciding the required transmission power. The performance of this fuzzy logic-based transmission power control (FTPC_MAC) scheme is compared with the standard IEEE 802.15.4 MAC protocol (IEEE_MAC) and also with location prediction-based transmission power control (LPTPC_MAC). Analytical and simulation results show that fuzzy logic-based transmission power control performs better than the other two MAC protocols.